PURWARUPA FRAMEWORK APLIKASI DESKTOP MENGGUNAKAN TEKNOLOGI WEB - , Firmansyah Adiputra; , Dr. techn. Khabib Mustofa, S.Si., M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Desktop application is an application that runs locally in a desktop environment and can be accessed only by the desktop user that executes it. It differs from web application which can be accessed from anywhere through networks. But unlike desktop applications, web applications cannot integrate nicely with desktop applications from where it is accessed. If an application can have not only desktop applicationâs capabilities, but also can be accessed through networks, then while it is disconnected from networks, it still can be accessed locally and still can integrate with other desktop applications. But when it is connected, it will have abilities to be remote controlled, providing additional services which are suitable only if accessed from network, or even disables its services which are not safe to be accessed from network. This research developes a prototype of framework which is named HAF (Hybrid Application Framework). HAF is a framework for developing and executing a new type of desktop application which in this research is called HyApp (Hybrid Application). Through HAF, HyApp is built using web technologies and can be accessed either locally or through networks. When accessed locally, eventhough it is built using web technologies, it still can communicate with other desktop applications. Also by using APIs provided by HAF, HyApp is capable to behave differently based on whether it is accessed locally or remotely.